2013
DOI: 10.1111/jocn.12068
|View full text |Cite
|
Sign up to set email alerts
|

Reducing interruptions to continuous enteral nutrition in the intensive care unit: a comparative study

Abstract: Review of practice may reveal opportunities for improvement. Nurse champions can facilitate change processes to improve care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
0
16
0
5
Order By: Relevance
“…They found that a nursing clinical decision support system integrated into the electronic flow sheet increased adherence to guidelines. Change champions have been shown to facilitate change processes to improve care 11 , 16 . This is a role that can be played by appropriate staff who take an active interest in and accountability for enhancing practice.…”
Section: Section 6 Administration: Generalmentioning
confidence: 99%
See 3 more Smart Citations
“…They found that a nursing clinical decision support system integrated into the electronic flow sheet increased adherence to guidelines. Change champions have been shown to facilitate change processes to improve care 11 , 16 . This is a role that can be played by appropriate staff who take an active interest in and accountability for enhancing practice.…”
Section: Section 6 Administration: Generalmentioning
confidence: 99%
“…However, these therapies are essential in some situations because irreversible hypoxic brain injury trumps the risk of potential aspiration. High‐flow volumes by noninvasive ventilation (NIV), noninvasive positive pressure ventilation (NIPPV), or other means can increase the risk of aspiration, and the risk is further increased in the sedated patient 16 . EN is not always indicated in patients on high‐flow volume NIV as some patients have learned to eat with high‐flow volume NIV without incidence of pneumonia, including patients with neuromuscular diseases such as amyotrophic lateral sclerosis.…”
Section: Section 6 Administration: Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…In the bicarbonate and saline groups these scores were higher on the last day than the first day in the enterally fed patients. In literature, it has been reported that parenteral nutrition has more disadvantages due to severe complications that may arise as compared to enteral nutrition (Cherry‐Bukowiec, ; Williams et al ., ). In our study, we also found that the oral mucosa of patients who received parenteral nutrition in the chlorhexidine group was in poorer condition than the ones who received enteral nutrition.…”
Section: Discussionmentioning
confidence: 97%